Cancer cell invasion and EMT marker expression: a three‐dimensional study of the human cancer–host interface. Issue 3 (November 2014) - Bronsert, P; Enderle‐Ammour, K; Bader, M; Timme, S; Kuehs, M; Csanadi, A; Kayser, G; Kohler, I; Bausch, D; Hoeppner, J; Hopt, UT; Keck, T; et al.
Abstract Cancer cell invasion takes place at the cancer–host interface and is a prerequisite for distant metastasis. The relationships between current biological and clinical concepts such as cell migration modes, tumour budding and epithelial–mesenchymal transition (EMT) remains unclear in several aspects, especially for the 'real' situation in human cancer. We developed a novel method that provides exact three‐dimensional (3D) information on both microscopic morphology and gene expression, over a virtually unlimited spatial range, by reconstruction from serial immunostained tissue slices. Quantitative 3D assessment of tumour budding at the cancer–host interface in human pancreatic, colorectal, lung and breast adenocarcinoma suggests collective cell migration as the mechanism of cancer cell invasion, while single cancer cell migration seems to be virtually absent. Budding tumour cells display a shift towards spindle‐like as well as a rounded morphology. This is associated with decreased E‐cadherin staining intensity and a shift from membranous to cytoplasmic staining, as well as increased nuclear ZEB1 expression. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.